Proposição de um modelo integrativo de justiça para o sistema agregado de marketing turístico - Medeiros, Fabiana Gama de (2017)
The presented work aimed to outline the development of an Integrative Justice Model (IJM) for the Aggregate Tourist Marketing System (ATMS). It draws on the tradition of macromarketing ethics studies, from a theoretical construction, together with an empirical research of a specific tourist marketing system. We therefore argue for the need to establish justice principles suitable to promote a fair and balanced functioning within the tourist marketing system. Thus for, the following objectives were outlined: discuss balance in marketing systems in a general matter, based on justice and stakeholder theories; better understand specific tourism characteristics in the sense of subsequently subsidizing the construction of justice principles adaptable to aggregate marketing systems of this nature; and understand the functioning of a specific marketing system, under which we could base - together with the theoretical contribution - for the proposition of the integrative justice model. In order to achieve those objectives, we initially carried out a theoretical study discussing justice and stakeholder theories, as foundations for promoting a fair marketing system. Then we have analyzed conceptual tourism elements and the constitution of the Aggregate Tourist Marketing System, and additionally, we have undertaken an empirical study in the tourist region of Brejo, in the state of Paraíba, Brazil, in order to ground the theoretical basis for the design of justice principles suitable to such systems. As a result, we could synthesize the proposition of the Integrative Justice Model for the ATMS, not only in normative manner, but also through the proposition of practical actions for the justice principles to be taken by system’s stakeholders. As main contributions of our proposal, we firstly bring the perspective of aggregate marketing system into the tourist activity, in terms of macromarketing ethics and marketing systems balance, and, secondly, by proposing an applicable Integrative Justice Model to the ATMS, in which we outlined principles for a balanced functioning, as well as paths for the practical structuring of actions which enable the IJM principles accomplishment. We believe that this type of system works more efficiently insofar as it establishes collaborative actions among its stakeholders, taking into account the interests of local residents and reducing the system’s dependence on the government.